2022
DOI: 10.1038/s41598-022-25222-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of double functionalized carbon nanotube for amphotericin B and genetic material delivery

Abstract: In the present work, single wall carbon nanotubes (SWCNT) were successively functionalized with phospholipid DSPE-PEG carboxylic acid, and then, with ethylenediamine (EDA), to obtain double functionalized single wall carbon nanotube (DFSWCNT). Then, DFSWCNT was applied as a carrier for delivering amphotericin B (Amb) and EGFP plasmid. FSWCNT’s concentration obtained via UV–visible analysis was 0.99 mg/mL. The TGA analysis results provided the lost weights of DSPE-PEG-COOH, EDA, Amb and SWCNT impurities. XPS re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…This analysis demonstrated that upon increasing the CD47_siRNA : GO ratio, it is possible to obtain a higher transfection efficiency, as observed in other studies. 15,68,69 GO thus proves to be a potentially viable alternative to chemically modified GO. This alternative might be preferable in some cases because unmodified GO, such as sGO, is less processed and therefore less expensive and complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis demonstrated that upon increasing the CD47_siRNA : GO ratio, it is possible to obtain a higher transfection efficiency, as observed in other studies. 15,68,69 GO thus proves to be a potentially viable alternative to chemically modified GO. This alternative might be preferable in some cases because unmodified GO, such as sGO, is less processed and therefore less expensive and complex.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis demonstrated that upon increasing the CD47_siRNA : GO ratio, it is possible to obtain a higher transfection efficiency, as observed in other studies. 15,68,69 GO…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…[ 93,94 ] The zero‐order model has a constant drug release rate across time, whereas in the first‐order model, the release of the drug is directly proportional to the drug concentration. [ 94 ] The Higuchi model explains the release rate as a function of the square root of time, and its generalized model is termed the Korsmeyer‐Peppas model. [ 94 ] The equations for all the models described above are: Zerobadbreak−Ordermodel;0.16emMtgoodbreak=Mgoodbreak+kt$$\begin{equation}{\mathrm{Zero}} - {\mathrm{Order model}};\,{{\mathrm{M}}}_{\mathrm{t}} = {{\mathrm{M}}}_\infty + {\mathrm{kt}}\end{equation}$$ Firstbadbreak−Order0.16emmodel;ln()Mt/Mgoodbreak=kt$$\begin{equation}{\mathrm{First}} - {\mathrm{Order}}\,{\mathrm{model}};{\mathrm{ln}}\left( {{M}_{\mathrm{t}}/{M}_\infty } \right) = kt\end{equation}$$ Higuchi0.16emmodel;Mt/Mgoodbreak=kt$$\begin{equation}{\mathrm{Higuchi}}\,{\mathrm{model}};{M}_{\mathrm{t}}/{M}_\infty = k\surd t\end{equation}$$ Korsmeyerbadbreak−Peppas0.16emmodel;ln()Mt/Mgoodbreak=lnkgoodbreak+nlnt$$\begin{equation}{\mathrm{Korsmeyer}} - {\mathrm{Peppas}}\,{\mathrm{model}};{\mathrm{ln}}\left( {{M}_{\mathrm{t}}{\mathrm{/}}{M}_\infty } \right) = {\mathrm{lnk}} + {\mathrm{nlnt}}\end{equation}$$where M t represents the absolute cumulative concentration of the drug released at time t , M ∞ represents the total cumulative concentration released after infinite time, k represents the release kinetic constant, and n represents the diffusion exponent parameter.…”
Section: Cnts: An Efficient and Promising System For Antifungal Drug ...mentioning
confidence: 99%
“…[92] Additionally, several mathematical operations include zero, first and second-order kinetics, Higuchi, Hixson-Crowell, Ritger-Peppas/Korsmeyer-Peppas (power-law model), and Weibull can be applied to illustrate the release mechanism. [93,94] The zero-order model has a constant drug release rate across time, whereas in the first-order model, the release of the drug is directly proportional to the drug concentration. [94] The Higuchi model explains the release rate as a function of the square root of time, and its generalized model is termed the Korsmeyer-Peppas model.…”
Section: Antifungal Drug Releasementioning
confidence: 99%
See 1 more Smart Citation